PENGARUH KEPEMIMPINAN TERHADAP KINERJA DAN STRES KARYAWAN (Studi Kasus : CV. Mertanadi) - Wiranata, Anak Agung (Jurnal Ilmiah Teknik Sipil; Vol. 15, No. 2 Juli 2011, 2012)
Leadership is considerably important in modern era organizations that requires democratization of working environment in a company. A poor leadership style may decline both employee and company's total performances. This study aims to determine the effect of leadership style on employee’s performance and level of stress. The hypotheses are: H0 = 0, the leadership does not affect the employee performance and level of stress while Ha ? 0, leadership affect the performance and stress level of employees. The results showed that for 5% error rate, leadership significantly affects the employee’s level of stress. The correlation of 0.47 (moderate correlation) indicating that the influence of leadership on employee’s level of stress on CV Mertanadi is 22.09%. At 5% error rate, leadership significantly affects the employee performances. The correlation of 0.73 (the strong correlation) indicating the influence of leadership on the performance of employees in the CV Mertanadi is 53.29%. This study concludes that the leadership affects both employees’s performance and level of stress.
Keywords: leadership, performance, stress